Medicinal Plants of the Lamiaceae Family in Namangan Region - Usmonov Tokhirjon; Zahiriddinov Ilyosjon (Scientific Trends, 2023)
The article provides information about medicinal plants belonging to the mint family distributed in the territory of Namangan region, the growing environment, soil conditions, chemical composition of the plant, and what purposes it is used in the national economy. economy. Based on this information, recommendations on plant cultivation and processing technologies are given.
Keywords: Lamiaceae, Medicinal plants, Mentha asatica Boriss, Origanum tytthanthum gontsch, Perovskia scrophulariifolia Bunge, Salvia sclarea L, Ziziphora pedicellata Pazij. & Vved, Ziziphora tenuior L, Phlomoides isochila, Phlomoides kirghisorum Adylov, Kamelin & Maxm.